Two new Mesoceration Janssens, 1967 from the Piketberg, South Africa (Coleoptera, Hydraenidae) - Bilton, David T.; Mlambo, Musa C. (Zootaxa, 2019)
Mesoceration explanatum sp. nov. and M. piketbergense sp. nov. are described from the Piketberg range in the Western Cape Province, South Africa, bringing the total number of known species in the genus to 55, all of which are endemic to South Africa. M. explanatum sp. nov. is a member of the truncatum group, whilst M piketbergense sp. nov. belongs to the endroedyi group and is apparently closely related to M. concessum Perkins & Balfour-Browne, 1994 and M. tabulare Perkins, 2008, both of which are endemic to the Cape Peninsula. The two new species were both relatively abundant in the Piketberg, and may be narrowly endemic to this inselberg-like mountain range.